Stinging wasps, ants and bees (Hymenoptera : Aculeata) of the Nenets Autonomous Okrug, northern Russia - Juho Paukkunen; Mikhail V. Kozlov (FINNISH ZOOLOGICAL BOTANICAL PUBLISHING BOARD, 2022)
Among Aculeata, only bumblebees (Bombus spp.) have long been popular targets of entomological research in the Russian Arctic, whereas the information on wasps, ants and solitary bees from this region is scarce. Sampling in the surroundings of Naryan-Mar in the years 2013, 2015 and 2019 yielded 39 species of Aculeata, among which 27 species are for the first time reported from the Nenets Autonomous Okrug (NAO). Noteworthy findings include Gorytes neglectus, Lasioglossum boreale, 3limumesa littoralis, Odynerus alpinus and Osmia maritima. Combined with published information, our data increased the fauna of aculeate Hymenoptera of NAO to 61 species. We also list and discuss erroneous or doubtful records of additional 11 species. Collection localities are provided for each species. Based on comparisons with northern Finland and the Murmansk Oblast in Russia we estimate that about 60 additional aculeate species could still be found in NAO.